Night of the living worms : a Speed bump and Slingshot misadventure - Coverly, Dave (New York : Henry Holt and Company, 2015)
Jealous of his brother, Early Bird, who always gets the worm, Speed Bump embarks on an adventure with his best friend Slingshot.
"Christy Ottaviano Books."
Keywords: Birds -- Juvenile fiction; Sibling rivalry -- Juvenile fiction; Brothers -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Birds -- Fiction; Sibling rivalry -- Fiction; Brothers -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Humorous stories; Humorous fiction